Religion and politics in the modern world - Kumar, Vikramendra (New Delhi Global Vision Publishing House, 2022)
This book religion and politics in the modern world offers students with an accessible yet in- depth introduction of the most important debates, issues and techniques in the field of religion and politics
Keywords: Religion; Politics; Caste- Hinduism- India